2015
DOI: 10.1016/j.fob.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Association between Apolipoprotein E polymorphism and myocardial infarction risk: A systematic review and meta‐analysis

Abstract: HighlightsThis study suggests that there is close association between ApoE polymorphism and MI risk.ApoE ε2 allele is a protective factor of MI.ε4 allele is a risk factor for MI, especially in Caucasian and Asian populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 37 publications
3
17
1
Order By: Relevance
“…Xu et al found similar results which showed that the ε4 allele had a 46% higher risk of CAD (OR = 1.46, 95% CI = 1.28–1.66) (Xu et al, 2016 ). Similar findings were also observed in other meta-analysis (Yin et al, 2013 ; Xu et al, 2014 , 2016 ; Zhang et al, 2014a , 2015 ; Wang et al, 2015b ). Interestingly, the role of APOE -ε2 allele in the risk of CAD may be dependent on the patient ethnicity (Xu et al, 2016 ).…”
Section: Discussionsupporting
confidence: 89%
“…Xu et al found similar results which showed that the ε4 allele had a 46% higher risk of CAD (OR = 1.46, 95% CI = 1.28–1.66) (Xu et al, 2016 ). Similar findings were also observed in other meta-analysis (Yin et al, 2013 ; Xu et al, 2014 , 2016 ; Zhang et al, 2014a , 2015 ; Wang et al, 2015b ). Interestingly, the role of APOE -ε2 allele in the risk of CAD may be dependent on the patient ethnicity (Xu et al, 2016 ).…”
Section: Discussionsupporting
confidence: 89%
“…Levels of plasma APOE and, generally also, high-density lipoprotein cholesterol (HDL-C) decrease in a perfect parametric fashion across the six APOE genotypes (2/2 > 2/3 > 2/4 > 3/3 > 3/4 > 4/4; Figure 4A), and the reverse is true for levels of low-density lipoprotein cholesterol (LDL-C; Figure 4B) (Bennet et al, 2007;Khan et al, 2013;Rasmussen, 2016). A similar stepwise pattern is seen in the risk for coronary artery disease (CAD) and myocardial infarction (MI), where APOE2 carriers have the least risk, APOE4 carriers have the greatest risk, and APOE3 carriers fall in the middle (Anand et al, 2009;Bennet et al, 2007;Wang et al, 2015;Xu et al, 2016; Figure 4E). For comparison, the risk for AD across genotypes is shown in Figure 4D.…”
Section: Cardiovascular Diseasementioning
confidence: 80%
“…Importantly, they also (A-E) Across all six combination of APOE alleles, clear parametric decreases can be observed for plasma APOE levels (A) and increases for low density lipoprotein cholesterol (LDL-C) levels [mean ± SEM] (B), while TG levels are marked by a U-shape (geometric mean ± SEM) (C), indicating risk for hypertriglyceridemia in APOE2 and APOE4 carriers (Rasmussen, 2016). The parametric association of APOE genotypes with lipid traits is also reflected in the association with risk, indicated by OR ± SE, for AD (pathologically confirmed, Caucasian subset; Farrer et al, 1997) (D) and myocardial infarction (MI) (Wang et al, 2015) (E). (F) While the APOE-related risk for AD follows APOE2 > APOE3 > APOE4, cerebral amyloid angiopathy (CAA) and related risk for intracerebral lobar hemorrhage display a U-shape (% probability of cases versus controls; median ± minmax), indicating increased risk for both APOE2 and APOE4 carriers (Biffi et al, 2010).…”
Section: Other Neurodegenerative Disordersmentioning
confidence: 99%
“…The other studied apolipoprotein ApoE is found in chylomicrons and intermediate density lipoprotein (IDL) that is essential for the normal catabolism of triglyceride-rich lipoprotein constituents and cholesterol metabolism [121]. The ApoE gene, mapped on chromosome 19q13.32 in a cluster with ApoC1 and ApoC 2, is highly polymorphic [122], with 3 major alleles according to the amino acids at positions 130 (rs429358; c.388 T > C) and 176 (rs7412; c.526C > T) in exon 4: ApoE 2 (cys130/cys176), ApoE 3 (cys130/arg176), and ApoE 4 (arg130/arg176) (ensemble.org).…”
Section: Discussionmentioning
confidence: 99%
“…The ApoE gene, mapped on chromosome 19q13.32 in a cluster with ApoC1 and ApoC 2, is highly polymorphic [122], with 3 major alleles according to the amino acids at positions 130 (rs429358; c.388 T > C) and 176 (rs7412; c.526C > T) in exon 4: ApoE 2 (cys130/cys176), ApoE 3 (cys130/arg176), and ApoE 4 (arg130/arg176) (ensemble.org). The ApoE polymorphisms were found to affect mRNA transcription and result in increased plasma cholesterol and triglyceride with impaired clearance of lipids from the bloodstream [121]. Moreover, knockout mice lacking ApoE developed extreme hypercholesterolemia after a high-fat diet [123].…”
Section: Discussionmentioning
confidence: 99%